Multiorifice acoustic microrobot for boundary-free multimodal 3D swimming - Nima Mahkam; Musab C. Ugurlu; Sandeep Kumar Kalva; Amirreza Aghakhani; Daniel Razansky; Metin Sitti (Proceedings of the National Academy of Sciences, 2025)
The emerging new generation of small-scaled acoustic microrobots is poised to expedite the adoption of microrobotics in biomedical research. Recent designs of these microrobots have enabled intricate bioinspired motions, paving the way for their real-world applications. We present a multiorifice design of air-filled spherical microrobots that convert acoustic wave energy to efficient propulsion through a resonant encapsulated microbubble. These microrobots can swim boundary-free in three-dimensional (3D) space while switching between various frequency-dependent locomotion modes. We explore the locomotion dynamics of microrobots with diameters ranging from 10 μm to 100 μm, focusing on their boundary-free 3D swimming and multimodal locomotion in response to acoustic stimuli below 1 MHz. Further, we elucidate the dynamics of these microrobots, featuring a single multiorifice cavity, which contributes to complex acoustic streaming and facilitates swift, unrestricted movements. Finally, we demonstrate that incorporating microrobots with additional nickel and gold layers significantly enhances their steering and visibility in optoacoustic and ultrasound imaging, enabling the development of the next generation of microrobots in healthcare applications.